Muscle strength variations of knee joint muscles in elite female handball players after pre-season conditioning - Gonosova, Z.; Stastny, P.; Belka, J.; Bizovska, L.; Lehnert, M. (Journal of Human Kinetics, 2018)
Monitoring seasonal variations in strength performance and the relative risk of injury indicators related to strength of hamstring (H) and quadriceps (Q) in female elite athletes is beneficial for the training process. The aim of this study was to examine and compare the level of muscle strength, the conventional ratio (HCONC/QCONC) as well as two functional and strength ratios reflecting the movement of knee extension (HECC/QCONC) and flexion (HCONC/QECC), and the bilateral percentage strength deficit (BSD) in elite female handball players. The concentric and eccentric isokinetic peak torque was measured at an angular velocity of 60°/s on three occasions (in-season cessation, 4 weeks of rest followed by 4 weeks of individual conditioning and 6 weeks of group conditioning) in eleven female handball players (age: 23.1 ± 3.5 years, body height: 1.73 ± 0.6 m). According to ANOVA results, the BSD of H muscles in the concentric mode decreased between the in-season cessation and the end of the pre-season, and HCONC/QCONC increased at the beginning of the pre-season and at the end of the pre-season in comparison with inseason cessation measurement. The effect size analyses showed that the off-season rest followed by 10 weeks of the conditioning programme increased Q and H strength in comparison with the previous season with a large effect. Coaches should include progressive conditioning in the pre-season phase to decrease the bilateral strength deficit and to support further conditioning development.